Effects of electrode position on tone-burst-evoked Auditory Brainstem Responses (ABR) in humans - Dzulkarnain, Ahmad Aidil Arafat; Tengku Zam Zam, Tengku Zulaila Hasma; Azed, Zakiah; Rahman Zuhri, Mohd Imran; Sulaiman, Nur Hafizah (IDOSI Publications, 2014)
The objective of this study is to investigate the influence of two different positions of the electrodes - forehead/ipsilateral mastoid (Ipsilateral montage) and forehead/nape of the neck (Vertical montage) - on the latency and the amplitude of tone-burst-evoked auditory brainstem responses (ABRs) in normally-hearing adults. This was achieved through the tone-burst stimuli of different carrier frequencies for the purpose of determining the best electrode position. A combination of quasi-experimental and repeated-measure study designs were used throughout the study. Participants were tested with 80, 50 and 30 dBnHL tone-burst stimuli (2-1-2, Blackman window) at the frequencies of 500 Hz, 1000 Hz and 2000 Hz and click stimuli using ipsilateral and vertical montages of the electrodes. Fourteen normal-hearing subjects (Three male and eleven female) aged between 22 and 29 years participated. The results showed that the ABRs wave V latency did not significantly differ for the different montages of the electrodes. This was true for all tone-bursts (500, 1000 and 2000 Hz) except for the 2000 Hz tone-burst at 50 dBnHL. The tone-burst-evoked ABR wave V amplitude was slightly higher in the vertical than the ipsilateral montage for the majority of the stimulus combinations. This study concluded that the tone-burst-evoked ABRs have higher wave V amplitudes when using the vertical electrode montage, (Whether statistically significant or not). The use of the vertical montage of the electrodes is therefore recommended in clinical practice, provided that the visual/subjective analysis technique is used.